Meningkatkan Kecerdasan Kinestetik Anak Usia Dini Melalui Kegiatan Ekstrakurikuler Tari di PAUD Tunas Insan Kamil Kota Serang Banten - Rosmaladewi, Lestari; Haila, Hidayatullah; Darmawan, Dadan (Peneliti.net, 2023)
Kinesthetic intelligence is closely related to students' psychomotor abilities. This study aims to find out is the increase in kinesthetic intelligence experienced by students after participating in dance extracurricular activities. This study uses evaluative qualitative research methods. The research targets were students who took part in dance extracurricular activities at PAUD Tunas Insan Kamil aged 4-6 years. Data collection was carried out by conducting interviews with dance extracurricular trainers, observing and documenting. Based on the results of the study, 8 out of 9 students experienced an increase in kinesthetic intelligence after carrying out routine exercises for 4 meetings with an average value of students' body coordination abilities in the category of growing asexpected and growing very well, balance ability is in the category of growing as expected, strength abilities are in the category of growing as expected andgrowing very well, agility abilities are in the category growing as expected and the ability to coordinate eyes, hands and feet is growing as expected and growing very well.